Investigating students' vocabulary learning through captioning in social media - Rini Setiawati; La Sunra (Center for Humanities and Innovation Studies, 2023)
This research aims to describe the students' perspective on the use of captions in social media in learning English vocabulary, the EFL teachers' perspective on the use of captions in social media in teaching vocabulary, and the impact of the use of social media as a teaching and learning tool for English vocabulary. This research is a descriptive qualitative research design. Purposive sampling was used to collect samples from the teachers and students at the XII grade of one of the Vocational High Schools in Makassar, South Sulawesi, Indonesia. The instruments used in this research were an interview protocol and an observation checklist. The data showed that all students perceived social media captions helped them acquire vocabulary since the content was engaging, the learning materials were well-presented, and plenty of resources were available. In addition, the teachers stated that online teaching and learning have several advantages and disadvantages when using some media as their teaching strategy. Finally, vocabulary learning through social media positively impacts students' acquisition of more vocabulary. Vocabulary learning through social media captions is important for increasing students' vocabulary. Both teachers and students agree that captions on social media are extremely useful in teaching and learning.